Analysis of Asphalt Pavement Structures Based on Structural Bearing Capacity Data (Proceedings of Faculty of Civil Engineering, 2020)
The assessment of pavement structural condition defines the total bearing capacity of the pavement, and is determined through the assessment of the mechanical properties of pavement structure layers. Deflection of the pavement structure is one of the important indicators of the structural bearing capacity of the pavement. It represents the elastic deformation of the pavement structure and is inversely proportional to the bearing capacity of the pavement. The amount of deflection can be determined theoretically, by using the laws of the theory of elasticity and knowing the material properties of the pavement structure, or empirically, by measuring the elastic deformation generated by a known static or dynamic load on the pavement surface, usually using a falling weight deflectometer device (FWD device). This paper describes the theoretical methods for determining the structural bearing capacity of pavement structure, with emphasis on deflection as the predominant technical parameter for determining the assessment of pavement structural condition. An empirical procedure for determining deflection and an overview of influencing factors on the measured amounts of deflection are described. The indices derived from the deflection measurements used to determine the structural assessment of the pavement are presented. On the example of the pavement structure condition analysis, carried out as part of the master thesis, the importance of the implementation of continuous measurement in order to determine the structural condition and assessment of the pavement structure is shown.
Keywords: deflection; pavement structure; structural bearing capacity